Sosialisasi Hukum Pekerja Migran Indonesia Terhadap Pemenuhan Hak-Hak Pekerja Di Klang Lama Malaysia - Siregar, Muhammad Farhan; Harisman, Harisman (Maslahah: Jurnal Pengabdian Masyarakat, 2024)
This community service aims to overcome problems faced by partners, namely Indonesian migrant workers in Klang Lama, Malaysia, related to fulfilling workers' rights. The importance of this topic arises because of the gap between the rights that migrant workers have and their understanding and access to these rights. The selection of this topic supports efforts to improve the welfare of Indonesian migrant workers and have a positive impact on the community in Klang Lama. The aim of the service is to increase migrant workers' understanding of their rights, provide better access to legal information, and ultimately ensure the fulfillment of these rights . The method used involves legal outreach to migrant workers in Klang Lama. The partners involved are groups of Indonesian migrant workers in the region. The results of the service show a significant increase in migrant workers' understanding of their rights, with an increase of 30% in relevant hard skills and soft skills. In addition, there is an increase in economic value by increasing migrant workers' access to jobs that suit their skills, making a positive contribution to the local economy. The importance of this result lies in improving the welfare and human rights of migrant workers, which in turn can create a positive impact on bilateral relations between Indonesia and Malaysia as well as improving Indonesia's positive image in the eyes of the world.